Autoimmune Hepatitis: Diagnostic Dilemma in the Setting of Suspected Iron Overload - In Chul An; Ashish K. Tiwari; Srujan Ameda; Heather S. Laird-Fick (Case Reports in Gastrointestinal Medicine, 2013)
Autoimmune hepatitis (AIH) is an inflammatory condition of the liver that has a multitude of clinical presentations from chronic hepatitis to acute fulminant hepatitis. AIH diagnosis is typically suspected after ruling out other causes of hepatitis (such as vial hepatitis, hemochromatosis, Wilson’s disease, and primary biliary cirrhosis) through serological tests and by findings of high titers of certain autoantibodies (ANA and anti-SMA for type 1 AIH and anti-LKM-1 for type 2 AIH). AIH like most inflammatory conditions is associated with increased ferritin levels (acute-phase reactant) but typically near-normal transferrin saturation. The presence of excessive ferritin level in absence of high-transferrin saturation helps differentiate secondary iron overload from hemochromatosis where transferrin saturation is typically high. We herein describe a case of AIH that presented with high ferritin levels and transferrin saturation suggesting a diagnosis of hemochromatosis and needed arduous work-up to arrive at accurate diagnosis of AIH.